IMPLEMENTATION OF COOPERATIVE LEARNING MODEL OF THINK PAIR SQUARE TYPE TO IMPROVE STUDENTS’ MATHEMATICS LEARNING OUTCOMES IN CLASS VII1 SMP NEGERI 3 PEKANBARU - Anggi; Nahor Murani Hutapea; Rini Dian Anggraini (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2020)
This research is a classroom action research that aimed to improve the learning process and improve student learning outcomes through the implementation of the Cooperative Learning Model of Think Pair Square type. This research was conducted in class VII1 of SMP Negeri 3 Pekanbaru in the odd semester of 2019/2020. The subjects of this study were 40 students consisting of 21 boys and 19 girls. The research was done in two cycles with each cycle consisting of three meetings and once quiz. The research instrument used learning devices and data collection instrument. Learning devices consist of syllabus, lesson plan, student worksheet. Data collection instruments consisted of observation sheets and learning outcomes tests. Based on data analysis of teacher and student activities, it appears that there was an improvement in the learning process after implementation of Cooperative Learning model of Think Pair Square type. The data obtained from the student mathematics learning outcomes test shows that the competence of knowledge increased in the frequency of students achieving minimum mastery criteria (KKM) before action (12 students) to first cycle (26 students) and to second cycle (31 students). The competence of skills increased in the frequency of students achieving KKM from the first cycle (28 students) and to second cycle (37 students). This study results indicated that the implementation of the Cooperative Learning model of think pair square type can improve the learning process and improve students’ mathematics learning outcomes of class VII1 SMP Negeri 3 Pekanbaru.